Real-world effectiveness of inactivated vaccine on COVID-19 patients with comorbidities - Hao Zhang; Hua-Fang Yan; Wu-Jun Xiong; Li-Li Gao (Journal of Infection in Developing Countries)
Introduction: Patients with underlying diseases do not respond adequately to vaccines. Thus, continued research on the effects of vaccination in patients with comorbidities is crucial to evaluate the necessity of vaccination in this population. This study assessed the protective effects of inactivated vaccines on the severity and prognosis of COVID-19 in patients with comorbidities.